Single low dose primaquine to reduce gametocyte carriage and Plasmodium falciparum transmission after artemether-lumefantrine in children with asymptomatic infection: a randomised, double-blind, placebo-controlled trial. Issue 1 (December 2016) - Gonçalves, Bronner; Tiono, Alfred; Ouédraogo, Alphonse; Guelbéogo, Wamdaogo; Bradley, John; Nebie, Issa; Siaka, Débé; Lanke, Kjerstin; Eziefula, Alice; Diarra, Amidou; Pett, Helmi; Bougouma, Edith; et al.
Abstract Background A single low dose (0.25 mg/kg) of primaquine is recommended as a gametocytocide in combination with artemisinin-based combination therapies forPlasmodium falciparum but its effect on post-treatment gametocyte circulation and infectiousness to mosquitoes has not been quantified. Methods In this randomised, double-blind, placebo-controlled trial, 360 asymptomatic parasitaemic children aged 2-15 years were enrolled and assigned to receive: artemether-lumefantrine (AL) and a dose of placebo; AL and a 0.25 mg/kg primaquine dose; or AL and a 0.40 mg/kg primaquine dose. On days 0, 2, 3, 7, 10 and 14, gametocytes were detected and quantified by microscopy, Pfs25 mRNA quantitative nucleic acid sequence based amplification (QT-NASBA), and quantitative reverse-transcriptase PCR (qRT-PCR). For a subset of participants, pre- and post-treatment infectiousness was assessed by mosquito feeding assays on days -1, 3, 7, 10 and 14. Results Both primaquine arms had lower gametocyte prevalences after day 3 compared to the placebo arm, regardless of gametocyte detection method. The mean (95 % confidence interval) number of days to gametocyte clearance in children with patent gametocytes on day 0 (N = 150) was 19.7 (14.6 – 24.8), 7.7 (6.3 – 9.1) and 8.2 (6.7 – 9.6) for the AL-placebo, the 0.25 mg/kg primaquine dose and the 0.40 mg/kg primaquine dose arms, respectively. While 38.0 % (30/79) of selected gametocytaemic individuals were infectious before treatment, only 1/251 participant, from the AL-placebo group, infected mosquitoes after treatment. Conclusions We observed similar gametocyte clearance rates after 0.25 and 0.40 mg/kg primaquine doses. Infectivity to mosquitoes after AL was very low and absent in primaquine arms. ClinicalTrials.gov Registration NCT01935882